The Effect Of Nurse's Knowledge, Attitude and Application About Patient Safety With Fall Risk Incidents - Romauli E.G. Siallagan (VitaMedica : Jurnal Rumpun Kesehatan Umum, 2024)
Patient safety encompasses a system of services designed to ensure that patients feel secure. This includes proper identification, learning from incidents, injury prevention due to errors, follow-up actions, risk analysis, patient incident assessment, and risk management related to reporting. Implementing solutions to minimize risks also involves preventing injuries caused by employee negligence in performing incorrect actions. The objective of this research is to determine the impact of nurses' knowledge, attitudes, and practices regarding patient safety on the risk of patient falls. The study design is quasi-experimental (Pre and Post Test Without Control). Data analysis utilized univariate and bivariate methods. In this study, 50 respondents participated in an intervention. The average pre-test and post-test scores were analyzed to evaluate the influence of nurses' knowledge, attitudes, and practices on patient safety concerning the incidence of fall risk. The results indicated that there was no significant influence of knowledge and application of patient safety on fall risk (p-Value 0.230 > 0.05). However, there was a significant influence of nurses' attitudes on fall risk events (p-Value 0.000 < 0.05).